OLIY TA’LIM O’QUV JARAYONIGA INNOVATSION TA’LIM TEXNOLOGIYALARINI QO’LLASH - TA’LIMDA SIFAT SAMARADORLIGIGA ERISHISHNING ASOSIY VOSITASI - Kamolov, I.R.; Kanatbayev, S.S.; Sayfullayeva, G.I. (SCIENCE and SOCIETY, 2017)
The article is devoted to the issues of using innovational educational technologies in the studying process at higher educational institutions. Social and economic development of our Republic depends on efficiency of using innovation educational technologies in teaching process in high educational institutions. Using innovation educational technology by professors and teachirs requires methodical prepation and is one of the actual issues today.
Keywords: innovation; innovation al education; process of education; education; teacher; pedagogical technology; debate; wave; particle; Venn Diagram; Solar system; planet Land; planet Mercury; planet Venus; portfolio; scholastic portfolio; portfolio of results; portfolio of works; portfolio of reviews; assesment